Taras Shevchenko Translated and Retranslated by Vera Rich: A Lifelong Search for Poetic Perfection - Kolomiyets, Lada (Respectus Philologicus, 2018)
[straipsnis ir santrauka anglų kalba]
Keywords: nėra